The impacts of the Covid-19 pandemic on micro, small, and medium enterprises in Asia and their digitalization responses - Tetsushi Sonobe; Asami Takeda; Susumu Yoshida; Hoa Thi Truong (Asian Development Bank Institute (ADBI), 2021)
Soon after the outbreak of the COVID-19 pandemic, many governments began extending financial and other forms of support to micro, small, and medium enterprises (MSMEs) and their workers because smaller firms are more vulnerable to negative shocks to their supply chain, labor supply, and final demand for goods and services than larger firms. Since MSMEs are diverse, however, the severity of the pandemic's impact on them varies considerably depending on their characteristics. Using online survey data of MSMEs from eight developing economies in South, Southeast, and Northeast Asia, this paper attempts to deepen our understanding of the impact of the pandemic on MSMEs, especially their employment, sales revenue, and cash flow. It also characterizes those firms that began participating in online commerce and tries to determine how their use of online commerce and their employment are related in this difficult time. This paper also examines the government support that MSMEs have received and the extent to which it has satisfied their support needs.
Keywords: D22; J63; L25; O53; 330; COVID-19; microsmall; and medium enterprises (MSMEs); layoffs; cash shortage; digitalization